2020
DOI: 10.18775/ijmsba.1849-5664-5419.2014.65.1001
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Teachers in Higher Education: An Empirical Study of Higher Education Institutions in Portugal

Abstract: Burnout is considered by the World Health Organization an extreme response to cumulative and prolonged occupational stress, with teachers being among the professionals most affected by it. This disease influences physical and psychological well-being, negatively affecting the relationship between teachers and students. It also compromises the quality of teaching, thus inducing absenteeism and increasing professional abandonment. Our study examines the degree of incidence of Burnout affecting Professors from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Finally, this identity is also determined by a loss of autonomy, the individualisation of work and by high levels of stress and anxiety. Regarding the latter, levels change depending on variables such as gender, years of experience or professional category (Bedoya et al, 2017;Teles et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this identity is also determined by a loss of autonomy, the individualisation of work and by high levels of stress and anxiety. Regarding the latter, levels change depending on variables such as gender, years of experience or professional category (Bedoya et al, 2017;Teles et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the reasons cited, two stand out: the lack of work experience, which generates insecurity and anxiety; and the enormous job insecurity in which they find themselves. Finally, authors such as Li and Kou (2018), and Silva and Oliveira (2019) and Teles et al (2020a) highlight being an academic between 36 and 45 years of age as variables favouring stress. The main reason for this lies in the enormous burden of responsibilities associated with senior academics.…”
Section: Difference In Stress Levels Among University Teachersmentioning
confidence: 97%
“…When instructors try to balance teaching and research, they experience burnout (Xu, 2019). Besides, the requirements needed have led university instructors to risk developing signs and symptoms of occupational burnout and stress (Teles et al, 2020). A study by Fern andez-Su arez et al (2021) found a high occurrence of burnout syndrome in university professors and a high risk of suffering from it.…”
Section: University Instructors' Burnoutmentioning
confidence: 99%